Pengaruh Kinerja Keuangan Dan Struktur Modal Terhadap Financial Distress Pada Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019 - Dicky Zuliansyah; Lestari Wuryanti; Rahyono Rahyono (Jurnal Ilmiah ESAI, 2023)
This study aims to determine the Effect of Working Capital to Total Assets, Ebit to Total Assets, EBT to Current Liabilities, Total Asset Turnover, and Capital Structure to Financial Distress in Banking on the Indonesia Stock Exchange (IDX) in 2017-2019. The object of this research is a banking company listed on the Indonesia Stock Exchange. Based on the Purposive Sampling method, the research sample was carried out on 66 banking samples listed on the Indonesia Stock Exchange (IDX) in 2017-2019. Hypothesis testing in this study was carried out using the logistic regression analysis method in the SPSS program application. The results showed that Working Capital to Total Assets had an effect on financial distress with a significant value of 0.001. The variable Ebit to Total Assets has no effect on financial distress with a significant value of 0.999. The EBT variable to Current Liabilities has an effect on financial distress with a significant value of 0.028. The variable Total Asset Turnover has an effect on financial distress with a significant value of 0.038. Capital Structure variable has no effect on financial distress with a significant value of 0.202.